Effect of additives on slip casting rheology, microstructure and mechanical properties of Si3N4/SiC composites - Shahrestani, Shohreh (ELSEVIER SCI LTD, 2020)
The SiC/Si3N4 composites were fabricated with sintering process. To produce SiC/Si3N4 composite components, slurry mixtures containing Si/SiC powders were used by the slip casting method. In order to investigate the effect of dispersants and additives on the rheological properties and the body casted, slurries with concentration of 70% solid weight were prepared. It included a mixture of silicon and silicon carbide with weight ratios of 30 wt% and 70 wt%, respectively, and various weight percentages of Ball clay as lubricant and Tiron (sodium salt of benzene disulfonic acid) as dispersant at pH value of 7. After preparing the green bodies by slip casting method by using plaster mold, the samples were sintered at 1450 degrees C inside an atmospheric-controlled furnace under a pressure of 0.12 MPa of nitrogen gas for 2 h. By examining the rheological properties of the slurry and the sintering properties, it was concluded that the best slurry was obtained in terms of viscosity, density, porosity and strength using 5 wt% Ball clay and 0.5 wt% Tiron. Phase transformations, microstructure and morphology of the sintered specimens were accomplished by Field Emission Scanning Electron Microscopy (FESEM) examination and X-ray diffraction experimental analysis. XRD and FESEM results demonstrated that the composite fabricated by slurry containing 5 wt% Ball clay and 0.5 wt% Tiron had the least porosity without SiO2 phase.